The protective activity of natural flavonoids against osteoarthritis by targeting NF-κB signaling pathway - Ye, Yongjun; Zhou, Jianguo (Frontiers in Endocrinology, 2023)
Osteoarthritis (OA) is a typical joint disease associated with chronic inflammation. The nuclear factor-kappaB (NF-κB) pathway plays an important role in inflammatory activity, and inhibiting NF-κB-mediated inflammation can be a potential strategy for treating OA. Flavonoids are a class of naturally occurring polyphenols with anti-inflammation. Structurally, natural flavonoids can be divided into several sub-groups, including ﬂavonols, ﬂavones, flavanols/catechins, ﬂavanones, anthocyanins, and isoﬂavones. Increasing evidence demonstrates that natural flavonoids exhibit protective activity against the pathological changes of OA by inhibiting the NF-κB signaling pathway. Potentially, natural flavonoids may suppress NF-κB signaling-mediated inflammatory responses, ECM degradation, and chondrocyte apoptosis. The different biological actions of natural flavonoids against the NF-κB signaling pathway in OA chondrocytes might be associated with the differentially substituted groups on the structures. In this review, the efficacy and action mechanism of natural flavonoids are discussed against the development of OA by targeting the NF-κB signaling pathway. Potentially, flavonoids become useful inhibitors of the NF-κB signaling pathway for the therapeutic management of OA.